2015
DOI: 10.1007/s11910-015-0527-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Insights into Insomnia

Abstract: Insomnia is one of the most prevalent health complaints afflicting approximately 10% of the population in Western industrialized countries at a clinical level. Despite the proposition that both biological and psychological factors play a role in the experience of insomnia, the field continues to puzzle over so-called "discrepancies" between objective and subjective measurements of sleep and daytime functioning. The promise of neuroimaging is to uncover physiological processes that may readily explain patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 86 publications
7
61
0
Order By: Relevance
“…25 A meta-analysis of subjective and objective measures in primary insomnia revealed a disproportionate increase of PSQI-reported disturbance relative to PSG findings. 26 A previous evaluation of TMD patients reported largely normal PSG findings in the context of elevated prevalence of primary insomnia diagnosis. 17,18 The present study provides further evidence for subjectively poor sleep without clear objective findings in TMD cases, a pattern consistent with chronic insomnia.…”
Section: Discussionmentioning
confidence: 92%
“…25 A meta-analysis of subjective and objective measures in primary insomnia revealed a disproportionate increase of PSQI-reported disturbance relative to PSG findings. 26 A previous evaluation of TMD patients reported largely normal PSG findings in the context of elevated prevalence of primary insomnia diagnosis. 17,18 The present study provides further evidence for subjectively poor sleep without clear objective findings in TMD cases, a pattern consistent with chronic insomnia.…”
Section: Discussionmentioning
confidence: 92%
“…The prefrontal cortex has demonstrated its important roles in alertness, attention, and higher-order cognitive processes for insomnia (Thomas et al, 2000; Spiegelhalder et al, 2015). Recently, Li et al demonstrated reduced ALFF values in the left IFG and right MFG in primary insomnia (PI) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the thalamus is a complex association of central nuclei that are closely correlated and interposed with the arousal and frontal systems, thus linking to the levels of vigilance and wakefulness of sleep (Bridoux et al, 2015). Overall, the insula of the salience network and the thalamus of the hyperarousal system are essential for insomnia, which indicates the hub of the insula and thalamus in sleep-related activity (Spiegelhalder et al, 2015). Using task-based fMRI, Bell-McGinty et al also discovered increased activation in the right putamen in subjects after total sleep deprivation (TSD), which revealed that changes in the arousal levels may affect performance following TSD (Bell-McGinty et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review focused on the neural mechanisms of insomnia points out that the alteration of the hyperarousal system (i.e., hypothalamus and brainstem), the reward and salience system (i.e., amygdala, hippocampus, and insula), and the cognitive control system can result in malfunctioning during the wake to sleep transition, sustained sleep difficulties, and cognitive impairment in insomnia. [14] In addition, converging evidence suggests that various core intrinsic connectivity networks are related to insomnia symptoms. Using optimized voxel-based morphometry, Altena et al [15] demonstrate that reduced gray matter volume in the left orbitofrontal cortex is positively associated with insomnia scores in insomnia patients, supporting the reward network as a plausible substrate for the insufficient problem-solving abilities of insomnia.…”
Section: Introductionmentioning
confidence: 99%